PERAN PANTI SOSIAL BINA REMAJA (PSBR) RUMBAI DALAM PEMBINAAN REMAJA PUTUS SEKOLAH - Winda Yulia Sari; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to find out the role of adolescent social institution (PSBR) Rumbai the development of teenagers dropout of school as well as to know the factors that support the implementation of the role of adolescent social institution (PSBR) Rumbai the development of teenagers dropout of school. This research uses descriptive qualitative research method. The subjects were chosen by purposive sampling technique. The subjects of this research are the employees who work in the adolescent social institution (PSBR) Rumbai which has been set previously amounted to 3 people, then the students who are being coached amounted to 2 people, and the students who have finished nurses amounted to 2 people. Technique of collecting data in this research is done by interview, observation, and documentation. The result of the research shows that the role activity of adolescent social institution (PSBR) Rumbai in the implementation of coaching drop out teenagers through two programs namely guidance program, and service program. The guidance activities provided include: physical guidance, social counseling, mental guidance, and skills guidance. Skills guidance provided include: sewing skills, makeup skills, welding engineering skills, and two-wheeled motor skills. Implementation of guidance activities tailored to the schedule that has been made. For instructors tutoring teachers come from employees PSBR Rumbai and also for guidance skills imported from outside the orphanage is the people who work with PSBR Rumbai. Determination of materials, methods, and learning media tailored to the activities of coaching. The supporting factors for the implementation of the Rural Teenage Youth Social Institution in the development of out-of-school youth are funding factors, human resource factors, facilities and infrastructure factors, and co-operation and outsiders.Key Words: Roles, Development, Teenage Drop Out Of School